Perlindungan Hukum Konsumen Pada Jual Beli Sistem Jasa Titip (Studi Kasus di Desa Rengaspendawa Kab. Brebes) - Annur, Najwa Neilal Muna; Aziz, Fikro Shulkhu; Setiawan, Diki Aji; Azkia, Erika Azkal (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
This study investigates the implementation of consumer protection in online transactions using jasa titip (personal shopping services) in Rengaspendawa Village, Brebes Regency. The issue arises due to the informal nature of these transactions, which often lack written agreements and legal awareness from both parties. The objectives of this research are to: (1) examine the actual practice of jasa titip in the local context, (2) assess the level of consumer legal protection based on Indonesian Law No. 8 of 1999 on Consumer Protection, and (3) analyze the relevance and application of the Islamic legal contract wakalah bil ujrah in these transactions. A qualitative descriptive method with a juridical-empirical approach was used, involving in-depth interviews with service providers and consumers, observations, and document analysis. Findings reveal that jasa titip practices are based on mutual trust and conducted through social media platforms such as WhatsApp and Instagram. However, most consumers and providers lack understanding of their legal rights and obligations, leading to potential legal vulnerabilities. Despite this, some actors show moral responsibility, including compensation for delivery failures. Although the transactions align with the principles of wakalah bil ujrah, the absence of formal contracts weakens their legal and sharia-based validity. This research highlights the urgent need for legal literacy, standardized procedures, and socialization to improve the professionalism and fairness of jasa titip systems.